Sosialisasi dan Skrining Tumbuh Kembang Anak dengan Kuesioner Pra Skrining Perkembangan (KPSP) pada siswa TK X Panyabungan - Mukhlis Mukhlis; Saidah Yustika; Jureid Jureid (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Early detection of growth and development is a crucial step in identifying potential developmental delays in early childhood. This activity aimed to increase parents' and teachers' knowledge of child developmental stages and to conduct developmental screening using the Pre-Screening Development Questionnaire (KPSP) for students of Kindergarten X Panyabungan. The methods used included education through lectures and discussions, followed by KPSP screening on 20 children with an average age of five. The assessment covered gross motor skills, fine motor skills, language, and social independence. The screening results showed that all children (100%) were in the "age-appropriate" category, with no "questionable" or "deviation" categories found. 85% of participants stated that this activity was beneficial and increased their knowledge of child development. This activity demonstrated that the KPSP is an effective early detection tool in the school environment and can strengthen collaboration between teachers and parents. It is recommended that schools conduct regular developmental monitoring and provide ongoing stimulation to support optimal child development.